Razonabilidad y método en Charles Peirce : algunas aproximaciones al ámbito científico y, en particular, al de las ciencias jurídicas - Velázquez, Hugo José Francisco (Sapientia, 2017)
Charles Sanders Peirce was a great American 19th century’s philosopher, scientific and logical; he is considered the father of the pragmatism and founder of the semiotic. We think that Peirce was an ahead of his time, since he anticipated many aspects and elements of the scientific current methodology, evidence of it are his similarities with Karl Popper and his critical rationalism. In this article I will try to explain the notion of abduction developed by Peirce, and then I confront her with the positivism and logical positivism’s ideas in order to show his relevancy for the scientific current method, in turn, I will show the proximity that exists between Peirce’s methodology and Popper’s methodology. On the other hand, I will examine the concept of rationality in Peirce’s thinking, which I will compare with the models of rationality of Positivism and Neopositivism. Finally, I will compare the concepts examined with his analogous ones in the juridical sciences in order to clarify some polemic questions arisen in them.